Risk factors of social anxiety in patients with essential tremor - Hou, Lijun; Lei, Xiaoguang (Frontiers in Psychiatry, 2023)
Objective To study the risk factors of social anxiety (SA) in essential tremor (ET) patients. Methods Motor, cognition, and SA were evaluated using the Fahn-Tolosa-Marin Tremor Rating Scale (FTMTRS), Mini-Mental State Examination (MMSE), and Liebowitz Social Anxiety Scale (LSAS) for each subject. The potential risk factors of SA in ET were analyzed using univariate analysis. Results A total of 80 ET patients and 85 healthy controls completed the evaluation. The LSAS evaluation showed that the prevalence of SA in the ET group was 48.8%, higher than that in controls (12.9%, P < 0.001). Female (OR = 4.959, P = 0.014), younger age (OR = 4.172, P = 0.037), and head tremor (OR = 4.707, P = 0.025) were risk factors of SA among ET patients. Conclusion SA is prevalent in patients with ET. Risk factors, such as female sex, age, and head tremor, should be considered for the prevention and intervention of SA in ET patients.